CROSS-PARADIGM SYNTHESIS: BIBLIOMETRIC MAPPING CONCEPT INTEGRATION SOCIAL EMOTIONAL LEARNING (SEL) AND VALUE-BASED CHARACTER EDUCATION IN GLOBAL SENIOR SECONDARY EDUCATION - Fera Fauziyatur Rohmah; Muhammad Arif Syihabuddin (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Growing attention to holistic student development has stimulated increasing scholarly interest in the relationship between Social Emotional Learning (SEL) and Value-Based Character Education (VBCE). Although both approaches share a common focus on fostering students’ emotional, social, and moral growth, they have frequently been examined as separate educational constructs, leaving their conceptual interconnections insufficiently explored. This study aimed to map research developments, dominant themes, and conceptual relationships between SEL and VBCE within the context of secondary education through a bibliometric approach. Data were drawn from Scopus-indexed publications published between 2021 and 2026 and selected using the PRISMA procedure, resulting in 10 core articles. In addition, 15 supporting scientific publications were included to enrich the interpretation of the findings. Bibliometric analysis was conducted using VOSviewer and Biblioshiny to identify publication trends, keyword relationships, and thematic structures within the field. The findings revealed growing academic interest in the integration of SEL and character education, particularly during the 2024–2025 period. Social Emotional Learning and Character Education emerged as the most dominant themes and were closely associated with emotional intelligence, moral education, value-based education, and student engagement. These findings suggest that socio-emotional competencies and character development are increasingly viewed as complementary dimensions that support holistic education. The resulting bibliometric mapping highlights the conceptual convergence between SEL and VBCE and underscores their relevance for strengthening secondary education through the balanced development of students’ emotional, social, and moral capacities. ABSTRAK Perhatian terhadap pengembangan peserta didik secara holistik mendorong meningkatnya kajian mengenai hubungan antara Social Emotional Learning (SEL) dan Value-Based Character Education (VBCE). Meskipun memiliki orientasi yang serupa dalam mengembangkan aspek emosional, sosial, dan moral peserta didik, kedua pendekatan tersebut masih lebih sering dikaji secara terpisah sehingga keterkaitan konseptualnya belum tergambarkan secara komprehensif. Penelitian ini bertujuan memetakan perkembangan penelitian, tema dominan, dan hubungan konseptual antara SEL dan VBCE dalam konteks pendidikan menengah atas melalui pendekatan bibliometrik. Data diperoleh dari publikasi terindeks Scopus periode 2021–2026 yang diseleksi menggunakan prosedur PRISMA hingga menghasilkan 10 artikel inti, serta didukung oleh 15 artikel ilmiah pendukung. Analisis dilakukan menggunakan VOSviewer dan Biblioshiny untuk mengidentifikasi tren publikasi, keterhubungan kata kunci, dan struktur tema penelitian. Hasil analisis menunjukkan peningkatan perhatian akademik terhadap integrasi SEL dan pendidikan karakter, terutama pada periode 2024–2025. Social Emotional Learning dan Character Education menjadi tema yang paling dominan serta terhubung erat dengan kecerdasan emosional, pendidikan moral, pendidikan berbasis nilai, dan keterlibatan peserta didik. Temuan ini menunjukkan bahwa kompetensi sosial-emosional dan pembentukan karakter semakin dipandang sebagai dua dimensi yang saling melengkapi dalam mendukung pendidikan holistik. Pemetaan yang dihasilkan menegaskan adanya konvergensi konseptual antara SEL dan VBCE serta relevansinya bagi penguatan pendidikan menengah yang lebih berorientasi pada perkembangan emosional, sosial, dan moral peserta didik.